OnabotulinumtoxinA for trigeminal neuralgia: a review of the available data - Pedro A. Kowacs; Marco A. T. Utiumi; Fábio A. Nascimento; Elcio J. Piovesan; Helio A. G. Teive (Arquivos de Neuro-Psiquiatria)
Trigeminal neuralgia (TN) patients may develop side effects from centrally acting drugs, have contraindications for neurosurgical procedures, or experience relapse during conventional therapies. OnabotulinumtoxinA (BoNT/A) has been reported to be effective for TN, although this finding has been challenged. An overview of the available evidence based on a narrative/qualitative analysis of the literature is presented. About 90% of patients who receive BoNT/A show an improvement, a higher figure than that reported for the placebo effect of BoNT/A for other headaches. Tolerability of BoNT/A is good, and its few side-effects are transient. The articles reviewed were mainly case reports, case series and open-label trials; however, randomized controlled trials have endorsed the efficacy of BoNT/A for TN. This evidence, together with a better understanding of the analgesic mechanisms of BoNT/A and its proven efficacy in treating other pain syndromes, supports the use of this toxin as a therapeutic option for TN.